Reaksi transfer hidrogenasi minyak jarak kastor serta aplikasinya sebagai bahan pelunak kompon karet - Puspitasari, Santi; Cifriadi, Adi; Krisnawati, Krisnawati; Irawadi, Tun Tedja (Majalah Kulit, Karet, dan Plastik, 2016)
Rubber plasticizer is used to improve rubber processability so as to shorten time and reduce energy consumption during compounding. In general, rubber plasticizer is nonrenewable and environmentally harmful petroleum derivatives due to the carcinogenic property. Environmentally friendly plasticizer can be produced by transfer hydrogenation of vegetable oil. The research was aimed to synthesize new rubber plasticizer from transfer hydrogenation of castor oil using diimide compound which was generated in situ by oxidation of hydrazine hydrate and hydrogen peroxide as well as the application of the new rubber plasticizer obtained on natural and synthetic rubbers compounding. The result showed that the optimum condition of transfer hydrogenation was achieved at a capacity of 1000 ml oil/batch, 40oC for 5 hours, and ratio hydrazine hydrate to hydrogen peroxide at 1:2 due to the hydrogenated castor oil (HCO) had the highest degree of hydrogenation and neutral pH. The application of 10 phr HCO had significant effect on the compounding of EPDM 6250 which was shown by shortest time and lowest energy of compounding, and also by the highest minimum torque modulus. In addition, the crosslink density of rubber vulcanizate which was formed during accelerated sulfur vulcanization was affected both by the addition of HCO and the saturation of the rubber being used.Keywords: environmentally friendly plasticizer, castor oil, diimide hydrogenation, rubber.Â